Accounting Contribution to Total Productive Maintenance - Agung Praptapa (EBBANK, 2011)
Accounting plays significant role in business. The increase of business competition increases the need to accounting that can be used as a tool to develop competitiveness. Increasing business’s competition calls companies to more be concerned about quality. Quality is a key source of competitive advantage, and studies have shown that quality is positively related to increased market share and profitability (Evans & Lindsay, 1996). Customer satisfaction is a crucial goal of the entire quality process (Scott, 1998). Quality is based on value, that is, the relationship of usefulness or satisfaction to price (Evans & Lindsay, 1996). Quality includes on time delivery, defect free products, and satisfying customer services.  Quality enhancement is under responsibility of all organizational members (Praptapa, 2009).There are many methods and management tools to ensure and enhance quality. The term Total Quality Management (TQM) is commonly used to denote the system of managing for total quality. As companies, especially manufacturing companies, realise that quality can be provided if production systems are working efficiently and effectively, then people pay more attention to the best utilisation of equipment. An approach to optimalize the relationship between people and the equipment on which they rely is known as Total Productive Maintenance or TPM.